2018
DOI: 10.1021/acs.chemrev.7b00535
|View full text |Cite
|
Sign up to set email alerts
|

Nonfullerene Acceptor Molecules for Bulk Heterojunction Organic Solar Cells

Abstract: The bulk-heterojunction blend of an electron donor and an electron acceptor material is the key component in a solution-processed organic photovoltaic device. In the past decades, a p-type conjugated polymer and an n-type fullerene derivative have been the most commonly used electron donor and electron acceptor, respectively. While most advances of the device performance come from the design of new polymer donors, fullerene derivatives have almost been exclusively used as electron acceptors in organic photovol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
1,170
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,509 publications
(1,177 citation statements)
references
References 435 publications
(813 reference statements)
6
1,170
0
1
Order By: Relevance
“…[25] Although both ternary OSCs and tandem OSCs could improve the power conversion efficiency (PCE) value to about 15%, the ternary strategy possessing simplicity of processing active layer exhibits great potential in R2R technology. [29] Especially, many researchers have realized the importance of miscibility in ternary OSCs, [28,[35][36][37] such as the appearance of Förster resonance energy transfer, [38] distribution of third additive on the interfaces of donor and acceptor, [39] formation of alloy with donor or acceptor, [36,37,40] etc. [6,[32][33][34] Unfortunately, most of the research work about how to select appropriate third additive is based on the trial and error strategy, which is a process of labor and time consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Although both ternary OSCs and tandem OSCs could improve the power conversion efficiency (PCE) value to about 15%, the ternary strategy possessing simplicity of processing active layer exhibits great potential in R2R technology. [29] Especially, many researchers have realized the importance of miscibility in ternary OSCs, [28,[35][36][37] such as the appearance of Förster resonance energy transfer, [38] distribution of third additive on the interfaces of donor and acceptor, [39] formation of alloy with donor or acceptor, [36,37,40] etc. [6,[32][33][34] Unfortunately, most of the research work about how to select appropriate third additive is based on the trial and error strategy, which is a process of labor and time consumption.…”
Section: Introductionmentioning
confidence: 99%
“…As stated, the enhancement is due to the decreased π-π stacking distance with higher domain purity and charge transport. [28,35] Thanks to the Ade's deep investigation, the Flory-Huggins interaction parameter χ was calculated by the melting-point depression method, [46] demonstrating that the two polymers of FTAZ and PDPP3T were completely miscible. [31] Zhang et al found that the p-DTS(FBTTH 2 ) 2 could also effectively increase the PCE value of PTB7-Th:PC 70 BM, stating the formation of miscible alloy between third additive and polymer by the differential scanning calorimetry (DSC) and wide-angle grazing-incidence X-ray scattering (GIWAXS) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…

the continued research has led to power conversion efficiencies (PCEs) over 11% for single-junction devices. [9][10][11][12][13][14][15][16] Noteworthy improvements have been made over the last few years, and state-of-the-art NFA-OSCs have been reported with PCEs over 16 %, thus outperforming their fullerene-based counterparts. [9][10][11][12][13][14][15][16] Noteworthy improvements have been made over the last few years, and state-of-the-art NFA-OSCs have been reported with PCEs over 16 %, thus outperforming their fullerene-based counterparts.

…”
mentioning
confidence: 99%
“…[6][7][8] However, this leads to large energy losses (>0.60 eV), as defined by E loss = E g opt − qV oc , (E g opt is the optical bandgap, V oc is the open-circuit voltage, and q is elementary charge), and limits the power conversion efficiency (PCE) to less than 12% [9][10][11][12][13][14] after decades of effort. [22][23][24][25][26][27][28][29][30][31][32][33] For such a material combination, a large ΔE LUMO always exists, which reduces the highest occupied molecular orbital (HOMO) offset [ΔE HOMO = E HOMO(D) − E HOMO(A) ] to minimize energy loss [34][35][36][37] while enhancing the light collection in near-infrared (NIR) [15][16][17][18][19][20][21] To form a complementary absorption, current popular NFA OSCs are based on the combination of a widebandgap donor and a narrow-bandgap acceptor.…”
mentioning
confidence: 99%